Pengembangan Bahan Ajar Aplikatif Kontekstual Pada Mata Kuliah Filsafat - Kamarudin Zaelani; Fathurrahman (Alpatih Harapan Semesta, 2025)
This study aims to develop contextual-applied teaching materials for the General Philosophy course in higher education. Philosophy courses are often perceived as difficult, abstract, and less relevant to contemporary life. Therefore, it is necessary to design teaching materials that are not only theoretical but also applicable and contextual. This research uses a Research and Development (R&D) approach with a qualitative descriptive method. Data were collected through observation, interviews, documentation, and questionnaires. The results show that contextual learning approaches can improve students’ understanding by connecting philosophical concepts with real-life situations. The developed teaching materials incorporate seven main components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. These components make philosophy learning more meaningful, practical, and relevant. The study concludes that contextual-applied teaching materials are feasible and effective for improving learning outcomes in philosophy courses.